Multicenter Clinical Evaluation of Modified Two-Tiered Testing Algorithms for Lyme Disease Using Zeus Scientific Commercial Assays - Sfeir, Maroun M; Meece, Jennifer K; Theel, Elitza S; Granger, Dane; Fritsche, Thomas R; Steere, Allen C; Branda, John A (Journal of clinical microbiology, 2022)
Modified two-tiered testing (MTTT) algorithms for Lyme disease (LD), which involve the sequential use of orthogonal enzyme immunoassays (EIAs) without immunoblotting, are acceptable alternatives to standard two-tiered testing (STTT; EIA followed by immunoblots) provided the EIAs have been FDA-cleared for this intended use. We evaluated four Zeus Scientific LD EIAs used in two distinct MTTT algorithms for FDA review. MTTT 1 used a VlsE1/pepC10 polyvalent EIA followed by a whole-cell sonicate (WCS) polyvalent EIA. MTTT 2 used the same first-tier EIA followed by separate IgM and IgG WCS EIAs. In a retrospective phase, we compared each MTTT algorithm to STTT using archived samples from LD patients or control subjects. In a prospective phase, we used the same algorithms to analyze consecutive excess samples submitted for routine LD serology to three clinical laboratories. For the retrospective phase, MTTTs 1 and 2 were more sensitive (56% and 74%) than STTT (41%; ≤ 0.03) among 61 patients with acute erythema migrans (EM). In LD patients with neuroborreliosis, carditis, or arthritis ( 75), sensitivity was comparable between algorithms (96 to 100%; = 1.0). Among 190 control subjects without past LD, all algorithms were highly and comparably specific (≥99%, = 0.48). For the prospective phase, ( 2,932), positive percent-agreement (PPA), negative percent-agreement (NPA), and overall agreement of MTTT 1 with STTT were 93%, 97.7% and 97.4% (kappa 0.80). MTTT 2 yielded higher PPA (98%) but lower NPA (96.1%) and overall agreement (96.2%, kappa 0.74; all < 0.05). Compared with STTT, both MTTT algorithms provided increased sensitivity in EM patients, comparable sensitivity in later disease and non-inferior specificity.